Data on the regulation of moesin and merlin by the urokinase receptor (uPAR): Model explaining distal activation of integrins by uPAR - Bernard Degryse; Mishan Britto; Chun Xu Shan; Robert G. Wallace; Keith D. Rochfort; Philip M. Cummins; Gerardene Meade; Ronan P. Murphy (Data in Brief, 2017)
The data presented herein are connected to our research article (doi: 10.1016/j.biocel.2017.04.012) [1], in which we investigated the functional connections between the urokinase receptor (uPAR), and the ezrin/radixin/moesin (ERM) proteins, moesin and merlin [1]. Firstly, a model of action is proposed that enlightens how uPAR regulates distal integrins. In addition, data show the effects of expressing wild-type moesin or permanently active T558D mutant of moesin on angiogenesis and morphology of human aortic endothelial cells (HAEC). Additional data compare the effects of urokinase (uPA, the main ligand of uPAR) on the same cells. Lastly, we provide technical data demonstrating the effects of specific siRNA for moesin and merlin on moesin and merlin expression, respectively. Keywords: Urokinase receptor, Moesin, Merlin, Angiogenesis, siRNA